Food processing technologies impact on product attributes - Jaiswal, Amit K. (Boca Raton CRC Press, 2017)
"Food Processing Technologies: Impact on Product Attributes covers a range of food processing technologies and their effect on various food product attributes, such as bioactive compounds, safety, and sensory and nutritional aspects of the food upon processing"--Provided by publisher.
Keywords: Food industry and trade; Food -- Technology